Kinetic Determination of Phenylhydrazine by its Catalytic Effect on the Reaction Between Tertrophene Blue and Bromate in Acidic and Micellar Medium - Keyvanfard, M.; Alizad, Kh. (Asian Journal of Chemistry, 2011)
A new, sensitive, simple, inexpensive and fast kinetic spectrophotometric method was developed for the determination of trace amounts of phenylhydrazine over the range of 1.5-15 nM. The method is based on the catalytic effect of phenylhydrazine on the reaction of tertrophene blue and bromate in acidic and micellar medium is reported. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of tertrophene blue at 632 nm with a fixed-time 0.5-2.0 min from initiation of the reaction. The detection limit is 0.6 nM and relative standard deviation of 3, 6 and 9 nM phenylhydrazine for 5 replicate measurements was 0.81, 0.40 and 1.04 %, respectively. The method was applied to the determination of phenylhydrazine in human serum and water samples.